Diversity of Francisella Species in Environmental Samples from Martha’s Vineyard, Massachusetts - Berrada, Zenda L. (Springer-Verlag, 2009)
We determined whether Francisella spp. are present in water, sediment, and soil from an active tularemia natural focus on Martha’s Vineyard, Massachusetts, during a multiyear outbreak of pneumonic tularemia. Environmental samples were tested by polymerase chain reaction (PCR) targeting Francisella species 16S rRNA gene and succinate dehydrogenase A (sdhA) sequences; evidence of the agent of tularemia was sought by amplification of Francisella tularensis-specific sequences for the insertion element ISFTu2, 17-kDa protein gene tul4, and the 43-kDa outer membrane protein gene fopA. Evidence of F. tularensis subsp. tularensis, the causative agent of the human infections in this outbreak, was not detected from environmental samples despite its active transmission among ticks and animals in the sampling site. Francisella philomiragia was frequently detected from a brackish-water pond using Francisella species PCR targets, and subsequently F. philomiragia was isolated from an individual brackish-water sample. Distinct Francisella sp. sequences that are closely related to F. tularensis and Francisella novicida were detected from samples collected from the brackish-water pond. We conclude that diverse Francisella spp. are present in the environment where human cases of pneumonic tularemia occur.